2014
DOI: 10.1007/s10646-014-1284-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mitochondrial DNA damage in little brown bats (Myotis lucifugus) collected near a mercury-contaminated river

Abstract: Historical discharges of Hg into the South River near the town of Waynesboro, VA, USA, have resulted in persistently elevated Hg concentrations in sediment, surface water, ground water, soil, and wildlife downstream of the discharge site. In the present study, we examined mercury (Hg) levels in in little brown bats (Myotis lucifugus) from this location and assessed the utility of a non-destructively collected tissue sample (wing punch) for determining mitochondrial DNA (mtDNA) damage in Hg exposed bats. Bats c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
26
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
10
26
3
Order By: Relevance
“…In an in vitro study, plausibility for mtDNA damage was established through microscopy images that depicted increased ROS in a qualitative manner and DNA damage co-occurring in cellular space with mitochondria (Sharpe et al 2012). In a field study, some evidence for increased mtDNA damage was obtained in bats from areas with high potential for Hg exposure, but individual-level correlations with Hg levels were poor (Karouna-Renier et al 2014). Here we report the first quantified impacts of mercury on mtDNA in controlled experiments in an in vivo model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro study, plausibility for mtDNA damage was established through microscopy images that depicted increased ROS in a qualitative manner and DNA damage co-occurring in cellular space with mitochondria (Sharpe et al 2012). In a field study, some evidence for increased mtDNA damage was obtained in bats from areas with high potential for Hg exposure, but individual-level correlations with Hg levels were poor (Karouna-Renier et al 2014). Here we report the first quantified impacts of mercury on mtDNA in controlled experiments in an in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that DNA damage is possible in fish-eating populations, in children, and most importantly at exposure levels lower than those known to adversely impact the nervous system (Franchi et al 1994, Amorim et al 2000, Cebulska-Wasiewska et al 2005, Di Pietro et al 2008, Al-Saleh et al 2012). The focus of previous studies has primarily been on impacts to the nuclear genome, with only one study to date reporting mtDNA impacts (Karouna-Renier et al 2014). Depending on the kind of damage, increased mtDNA damage and damage accumulation in the mitochondrial genome are possible as there are fewer DNA repair pathways in this organelle (Ledoux et al 1992, Scheibye-Knudsen et al 2015, Van Houten et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has identified multiple pathways through which mitochondria can be compromised, in particular, from pollutant exposures (Martinez and Greenamyre, ; Meyer et al, ; Brunst et al, ). Inference on the degradation of mitochondria following exposure to toxicants, such as organic chemicals, particulate matter, polycyclic aromatic hydrocarbons and cationic metals, has drawn largely upon controlled laboratory experiments using cell lines, model organisms or animal models (Bucio et al, ; Cakir et al, ; Karouna‐Renier et al, ; Sanders et al, ; Sanders et al, ). This study examines factors influencing mtDNA copy number (CN) and damage in a randomly selected human population in the Peruvian Amazon living in an area with extensive mercury contamination due to artisanal and small‐scale gold mining (ASGM).…”
Section: Introductionmentioning
confidence: 99%
“…Inference on the degradation of mitochondria following exposure to toxicants, such as organic chemicals, particulate matter, polycyclic aromatic hydrocarbons and cationic metals, has drawn largely upon controlled laboratory experiments using cell lines, model Additional Supporting Information may be found in the online version of this article. organisms or animal models (Bucio et al, 1999;Cakir et al, 2007;Karouna-Renier et al, 2014;Sanders et al, 2014a;Sanders et al, 2014b). This study examines factors influencing mtDNA copy number (CN) and damage in a randomly selected human population in the Peruvian Amazon living in an area with extensive mercury contamination due to artisanal and small-scale gold mining (ASGM).…”
Section: Introductionmentioning
confidence: 99%
“…But the levels of mtDNA damage exhibited weak correlations with fur and blood Hg levels and the mtDNA damage may not be connected to mercury contamination in the river (Karouna-Renier et al, 2014). In another study, Sharpe and colleagues demonstrated that mtDNA damage was created by thimerosal.…”
Section: Resultsmentioning
confidence: 99%